2023
DOI: 10.3390/ijms24044079
|View full text |Cite
|
Sign up to set email alerts
|

DIS3: The Enigmatic Gene in Multiple Myeloma

Abstract: Recent studies have revealed the genetic aberrations involved in the initiation and progression of various cancers, including multiple myeloma (MM), via next-generation sequencing analysis. Notably, DIS3 mutations have been identified in approximately 10% of patients with MM. Moreover, deletions of the long arm of chromosome 13, that includes DIS3, are present in approximately 40% of patients with MM. Regardless of the high incidence of DIS3 mutations and deletions, their contribution to the pathogenesis of MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…In addition to TET2 and NRAS, other mutated genes in the patient appeared to be indirectly associated with the development of BPDCN or MF. It has been reported that loss of function in DIS3 increases the RAS protein level in multiple myeloma cells, which promotes the development of cancer cells (44). CSMD1 is a tumor suppressor gene, and dysregulation of CSMD1 can drive the NF-κB pathway and promote tumor progression (45).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to TET2 and NRAS, other mutated genes in the patient appeared to be indirectly associated with the development of BPDCN or MF. It has been reported that loss of function in DIS3 increases the RAS protein level in multiple myeloma cells, which promotes the development of cancer cells (44). CSMD1 is a tumor suppressor gene, and dysregulation of CSMD1 can drive the NF-κB pathway and promote tumor progression (45).…”
Section: Discussionmentioning
confidence: 99%
“…Controlled degradation of unnecessary RNA transcripts by the DIS3 family is essential for cell division and mitosis in eukaryotic cells. During the posttranscriptional regulation of gene expression, DIS3 family members are involved in the degradation of dispensable RNAs via their highly conserved 3′–5′ exoribonucleolytic activity 223 , 224 . The DIS3 family comprises three homologs, DIS3, DIS3L, and DIS3L2, in humans 225 , 226 .…”
Section: Dis3 3′–5′ Exoribonuclease Familymentioning
confidence: 99%
“…The two tandem CSDs and the C-terminal S1 domain confer substrate RNA binding. The PIN domain is located in the N-terminus of DIS3 and DIS3L but not DIS3L2, which endows DIS3 and DIS3L with endonucleolytic activity and tethers DIS3 and/or DIS3L to the nine-subunit core (EXO9) in the RNA exosome complex 224 . DIS3L is also known to have defective endonuclease activity because of the alteration of two essential catalytic residues within its PIN domain.…”
Section: Dis3 3′–5′ Exoribonuclease Familymentioning
confidence: 99%
See 1 more Smart Citation
“…Deletions of chromosomal fragments, like del(13q), are also frequently observed, especially in non-HRD MM 8 . However, their role in disease progression is less well-defined 9,10 . Mutations or chromosomal abnormalities detected at the MGUS stage are considered primary events involved in tumor development.…”
Section: Introductionmentioning
confidence: 99%